Colorimetric 3D printable base-detectors exploiting halocromic core-substituted naphthalenediimides. Issue 11 (22nd February 2023) - Tosetto, Beatrice; Gastaldi, Matteo; Renno, Giacomo; Pirri, Candido Fabrizio; Barolo, Claudia; Fin, Andrea; Roppolo, Ignazio
Abstract : Naphthalenediimide dye was used to fabricate polymeric 3D printed colorimetric sensors for bases, to detect aqueous, vapor and organic phases. Abstract : 3D printing field is in rapid evolution, and its applications are widening continuously. Among the different techniques available, light induced vat-methods are demonstrated to be particularly suitable for developing functional devices due to their superior precision and their high flexibility in terms of materials properties. An emerging strategy for imparting functional properties consists of the use of functional dyes, which can confer peculiar properties even at low contents, improving at the same time polymerization control and printing precision. Herein, an ad-hoc synthesized core-substituted naphthalene diimide (cNDIs) dye is investigated as a functional dye for Digital Light Processing 3D printing, to give pH sensitivity properties to complex objects. The employed cNDI shows multi-color responsivity towards different conditions, spanning from yellow to blue. Different 3D printable matrices are here compared, and among those poly(ethylene glycol) diacrylate is selected since it maximizes the dye response when in contact with acid/basic solutions, also showing good miscibility, fast photopolymerization kinetics, and excellent CAD fidelity of the 3D printed structures. Furthermore, it is also demonstrated that the 3D printed structures are responsive to basic vapors, as well as to organic solution containing Lewis bases. These results go far beyond standard use of pH-responsive dyes, opening up to new and wider applications. At last, stimuli-responsive 3D devices are fabricated, producing smart lab-ware and microfluidic devices which can give in operando visual responses towards basic vapors and basic organic solutions.